Design of a Plastic Waste Shredder Machine for the Processing of Inorganic Waste at TPS3R in Kudus Regency - Prasetia, Ary Putra; Yusron, Mohammad Aunun; Izzhati, Dwi Nurul (LPPM Telkom University Surabaya, 2024)
In 2022, Kudus Regency produced 4,300.52 tons of inorganic waste, primarily plastic. A plastic waste shredder machine was designed to address this issue at Integrated Waste Processing Sites (TPS3R). This research aims to reduce the volume of plastic waste sent to landfills and increase the economic value of recycled materials, ultimately enhancing waste management efficiency in Kudus Regency. This study employed an Ergonomic Anthropometry method to create a user-friendly design based on the physical characteristics of workers. The machine was tested at TPS3R Rendeng and successfully shredded plastic waste into small pieces, facilitating the recycling process. The machine, with a shredding capacity of 35-40 kg per hour and a maximum shred size of 15 mm, was developed using ergonomic anthropometric data from TPS3R workers. The design features a frame height of 106 cm, a width of 78 cm, and a length of 170 cm to ensure optimal usability. Additionally, this plastic shredder contributes to more efficient waste management in the Kudus Regency by reducing the load on landfills and supporting more sustainable recycling efforts.